Klasifikasi Layanan bagi Tamu Undangan Walimatul ‘Urs di Kecamatan Kota Nopan, Kabupaten Mandailing Natal Perspektif Hukum Keluarga Islam - Mukhliza, Lia; Irwan, Irwan (UNES Law Review, 2023)
Basically, the invited guests of “Walimatul ‘Urs” must be respected and treated equally without being differentiated from the others. Distinctions may be made based on the law propriety, such as giving priority to older people than young people, but in various villages in Kota Nopan District, Mandailing Natal Regency, recently on a massive scale, the classification of invited guests based on where thr guests come from will be differentiated between local people and people from a far, this case with never applicated previously. This research attempted to investigate the background factors of community’s behavior and put the law into the perspective of Islamic Family Law. The research method used is an empirical research method with a qualitative approach.